The effect of the entrepreneurial ecosystem of universities on the innovative activity in Russian regions - Olga A. Myzrova; Tatyana V. Goryacheva; Olga V. Sysoeva; Victor V. Sysoev (Economies, 2023)
The entrepreneurial ecosystem of universities is frequently recognized to have a key influence on the innovative activity of the related regions. However, these relationships have not been explored in the scientific literature regarding Russia. Therefore, the current study aims to determine and identify the contours of the entrepreneurial ecosystem of domestic universities in terms of the innovative activity of subjects in Russian regions. The methodological toolkit covers methods for information processing such as monographic desk research, hierarchical cluster and correlation analyses, and comparative analysis. Applying a hierarchical cluster analysis, we grouped universities according to the level of entrepreneurial activity with the allocation of the average value in order to determine the existing correlations and elucidate the problems in involving university innovations in the ratings of innovative activity of regions. The results contribute to the development of existing approaches toward the study of the entrepreneurial ecosystems of universities through a deeper understanding of their role in stimulating the innovative activity of regions and transformation processes.
Keywords: 330; innovative activity; entrepreneurial ecosystem; interaction contours; innovative component; hierarchical cluster analysis; rating